Letter from P. D. Carey (Jun.), Hon. Secretary of the APL to T. G. Hickey - Anti-Partition League, APL (1939)
Typescript letter dated 21 April 1939, to T. G.Hickey, Hon. Secretary, Provisional National Executive, from P. D. Carey (Jun.), Hon. Secretary (Glasgow Area) of the APL, about forthcoming meeting in Manchester